ANALISIS KINERJA DOSEN PADA PROGRAM STUDI TERAKREDITASI PERGURUAN TINGGI SWASTA DI SULAWESI SELATAN - Baso Amang (Media Riset Bisnis & Manajemen, 2011)
The aims of the study were to discover the effect of (1) ability on working motivation and lecturer's performance directly and indirectly, (2) compensation on satisfaction, motivation and lecturer's performances directly and indirectly, (3) facilities on satisfaction, motivation and lecturer's performances directly and indirectly, (4) working environment on satisfaction, motivation and lecturer's performances directly and indirectly, (5) leadership on satisfaction, motivation and lecturer's performances directly and indirectly, (6) satisfaction on motivation and lecturer's performances directly and indirectly, (7) motivation on lecturer's performances at accredited field of study at private institution in South Sulawesi. The used data are primary data which was collected from 218 respondents. The analysis steps consist of first, confirmed factor analysis to investigate apropriate measurement and second step was the use Structure Equation Modelleing (SEM) to varify the model. The results of the study indicate that : (1) Ability, compensation, working environment, and leadership simultaneously have a positive and significant effect on lecturer's performances. (2) Compensation is the effected most dominantly to variable satisfaction. (3) Satisfaction is the effected most dominantly to motivation. (4) Motivation is the effected most dominantly to lecturer's performances at accredited field of study at private institution in South Sulawesi.Keywords: Ability, Compensation, Facilities, Working environment, Leadership, Satisfaction, Motivation, Lecturer's performance